Determination of the Neonicotinoid Thiacloprid in Vegetables by Using Photochemically Induced Fluorescence - Ruiz-Medina, Antonio; Jiménez-López, Julia; Llorent-Martínez, Euologio J. (Current Topics on Chemistry and Biochemistry Vol. 1, 2022)
We describe an automated luminescence sensor for measuring the insecticide thiacloprid, one of the most common neonicotinoids, in lettuce samples in this paper. The use of luminescence sensors has increased in the last decade, minimizing reagents consumption and increasing the degree of automation. To handle all solutions, a simple and automated manifold was built employing multicommutated solenoid valves. The analyte was on-line irradiated with UV light to produce a highly fluorescent photoproduct (\(\lambda\)exc/\(\lambda\)em = 305/370 nm/nm) that was then retained on a solid support placed in the flow-cell. A method detection limit of 0.24 mg kg-1 was achieved in real samples, fulfilling the Maximum Residue Limit (MRL) of The European Union for thiacloprid in lettuce (1 mg kg-1). It was possible to acquire a sample throughput of 8 samples per hour. Recovery studies were conducted at levels near to the MRL, yielding recovery yields of close to 100% and relative standard deviations of less than 5%. As a result, as an alternative to other existing approaches, this method might be used for routine quality control analyses.